Circular Logistics in the Construction Industry - An exploratory study based in a Swedish context - Andersson, Andreas; Söderberg, Alexandra (My University, 2022)
The construction industry faces great environmental challenges; the construction industry is one of the industries with the highest emission of greenhouse gases, as well as user of virgin materials. One way to reduce the environmental impact of the industry is through circular economy, which would reduce the need for virgin materials. In order to enable circular economy in the construction industry, the logistical system of the industry must be adapted. This study aspires to determine how circular logistics should be used in order to facilitate for circularity. As a result, interviews have been carried out with people who have experience from either circularity, sustainability or logistics in the construction industry. From these interviews, a network has been presented that is designed to describe the building blocks of a circular logistical network. Additionally, the main driving forces and hinders to work with circular logistics has been discussed. The study concludes that the construction industry lacks logistical performance, as well as actors with the knowledge and competence to operate in a circular logistical system. Furthermore, a circular logistics network must be constructed with the focus of keeping the value as high as possible between two construction clients. In addition, the actors that operate within the logistical network has to facilitate for larger quantities of reused materials. Finally, it must be economically viable for construction clients to adopt a more circular approach.